ASSESSMENT OF THE PHYSICAL ABILITY OF 5TH GRADE STUDENTS - P. Mavrudiev; D. Simenova (Trakia Journal of Sciences)
The purpose of the research is to establish and evaluate the current level of physical fitness of the students from the two studied groups (boys and girls), as well as the individual assessments of the studied individuals. The object of research is the main signs of physical ability in students of both sexes. The following research methods are applied -research of literary sources, sports-pedagogical testing and analysis. The results of the research were subjected to mathematical-statistical processing through variational analysis and the sigma evaluation method. We found that the average score for the physical performance of boys was lower than that of girls, but both studied populations had a higher current level of development of physical capacity in comparison to the average for Bulgaria.